證明: 設tanA=a,tanB=b,tanC=c 則A,B,C∈(0,π/4) 2A,2B,2C∈(0,π/2), 將tanA,tanB,tanC代入ab+bc+ca=1 得tanAtanB+tanBtanC+tanCtanA=1 tanC=(1-tanAtanB)/(tanA+tanB) cot(π/2-C)=tanC=cot(A+B) π/2-C=A+B+kπ,k∈Z, 又A、B、C∈(0,π/4), 從而π/2-C∈(0,π/2),A+B∈(0,π/2) 則π/2-C=A+B 因此A+B+C=π/2,2A+2B+2C=π 原式左邊=(1/2)(tan2A+tan2B+tan2C) 在(0,π/2)上利用琴生不等式[設f(x)為凸函式,則f[(x1+x2+……+xn)/n]≤[f(x1)+f(x2)+……+f(xn)]/n(下凸); 設f(x)為凹函式,f[(x1+x2+……+xn)/n]≥[f(x1)+f(x2)+……+f(xn)]/n(上凸),稱為琴生不等式。 ] 得(1/2)(tan2A+tan2B+tan2C)≥(1/2)*3tan[(2A+2B+2C)/3]=(3/2)tan(π/3)=(3/2)*√3 ∴a/(1-a^2)+b/(1-b^2)+c/(1-c^2)>=3√3/2
證明: 設tanA=a,tanB=b,tanC=c 則A,B,C∈(0,π/4) 2A,2B,2C∈(0,π/2), 將tanA,tanB,tanC代入ab+bc+ca=1 得tanAtanB+tanBtanC+tanCtanA=1 tanC=(1-tanAtanB)/(tanA+tanB) cot(π/2-C)=tanC=cot(A+B) π/2-C=A+B+kπ,k∈Z, 又A、B、C∈(0,π/4), 從而π/2-C∈(0,π/2),A+B∈(0,π/2) 則π/2-C=A+B 因此A+B+C=π/2,2A+2B+2C=π 原式左邊=(1/2)(tan2A+tan2B+tan2C) 在(0,π/2)上利用琴生不等式[設f(x)為凸函式,則f[(x1+x2+……+xn)/n]≤[f(x1)+f(x2)+……+f(xn)]/n(下凸); 設f(x)為凹函式,f[(x1+x2+……+xn)/n]≥[f(x1)+f(x2)+……+f(xn)]/n(上凸),稱為琴生不等式。 ] 得(1/2)(tan2A+tan2B+tan2C)≥(1/2)*3tan[(2A+2B+2C)/3]=(3/2)tan(π/3)=(3/2)*√3 ∴a/(1-a^2)+b/(1-b^2)+c/(1-c^2)>=3√3/2